Ventromedial prefrontal cortex generates pre-stimulus theta coherence desynchronization: A schema instantiation hypothesis. (February 2017) - Gilboa, Asaf; Moscovitch, Morris
Abstract: The ventral medial prefrontal cortex (vmPFC) has long been implicated in monitoring of memory veracity, and more recently also in memory schema functions. In our model of strategic retrieval the two are related. We have proposed that the vmPFC has two schema-dependent functions: (i) to establish context-relevant templates against which the output of memory systems can be compared; (ii) to mediate automatic decision monitoring processes to ensure that only those responses that meet the criterion are enacted. Electroencephalogram (EEG) data were used to provide evidence that vmPFC supports both functions, and that schema instantiation informs monitoring. Participants viewed pictures of acquaintances, along with those of famous and nonfamous people, and were asked to respond positively only to pictures of individuals they had met ( personal familiarity) . The Self serves as a super-ordinate cognitive schema, facilitating accurate endorsement of acquaintances and exclusion of non-personal but familiar faces. For the present report we focused on pre-cue tonic oscillatory activity. Controls demonstrated theta coherence desynchronization between medial prefrontal areas, inferotemporal and lateral temporal cortices. These oscillatory coherence patterns were significantly reduced in patients with vmPFC damage, especially in those with clinical histories of spontaneous confabulation. Importantly, these pre-stimulus cortico-cortical desynchronizations predicted post-cue automatic memory activation, as indexed by a familiarity modulation of the face-sensitive posterior cortical N170. Pre-cue desynchronization also predicted early post-cue frontal positive modulation (P230) and response accuracy. The data are consistent with a schema instantiation model that suggests the vmPFC biases posterior neocortical long-term memory representations that enhance automatic memory cue processing and informs frontally-mediated rapid memory monitoring (P230). Damage to these structures can lead to inaccurate, context-irrelevant activation of schemas. These, in turn, impair monitoring signals and can lead to confabulation when memory control processes are also deficient.